Temporal analysis of mangrove carbon stock using Sentinel-2 data on Menjangan Island, West Bali National Park, Indonesia - Salsabila Ranti Dwimarsa; Panjaitan James Parlindungan (BIO Web of Conferences)
Mangrove forests are vital for their ecological function as the largest carbon storage systems in tropical regions, making a significant contribution to reducing carbon emissions. The mangrove areas in Menjangan Island part of the West Bali National Park (TNBB), are protected conservation zones that face various threats. This study aims to evaluate the changes in mangrove extent based on density, map actual biomass, estimate total carbon reserves, and analyze the relationship between changes in density and total carbon stock and sequestration in 2019 and 2023 using Sentinel-2 imagery. The NDVI-based classification data were categorized into three density classes by the Indonesian Forestry Ministerial Regulation (2012). Actual biomass values were derived using species-specific allometric methods with purposive random sampling. Biomass mapping was modeled with a simple linear regression equation using NDVI and actual biomass, resulting in the equation y = 1578,2x – 269,79 with an R2 of 82,81%. The result showed decline in mangrove carbon reserves on Menjangan Island decreased from 124,075 x 103 tonsC in 2019 to 105,705 x 103 tonsC in 2023, indicating a positive correlation between mangrove area changes, total carbon reserves, and carbon sequestration.